Students Teachers’ Self- Efficacy and Teaching Effectiveness - Siti Safura; Cut Mawar Helmanda (International Journal of English Education and Linguistics (IJoEEL), 2022)
This study concerned to the experience of students who had completed the teaching practice as their task in university. This study aims to discuss how self-efficacy influences teaching effectiveness, specifically at initial teaching of their teaching practice. The phenomenological approach as part of qualitative research was applied to see the students’ experience during teaching practice. The sample was four students at English Department, University of Muhammadiyah, Aceh that selected purposively. The four students were interviewed pertaining to five aspects: the importance of self-efficacy, promoting students’ learning, classroom management, building self-efficacy, and teaching ability. To interpret the interview data, the Huberman’ concept was proposed. The finding revealed that the self-efficacy outlines the advantageous for student teachers who were unversed in teaching-learning process. This self-efficacy helped them to have the braveness and the eagerness in increasing the teaching ability that positively affected their teaching effectiveness.